The roles of surrounding 2D/3D landscapes in park cooling effect: Analysis from extreme hot and normal weather perspectives. (1st March 2023) - Han, Dongrui; Xu, Xinliang; Qiao, Zhi; Wang, Fei; Cai, Hongyan; An, Hongmin; Jia, Kun; Liu, Yihui; Sun, Zongyao; Wang, Shihao; Han, Wei
Abstract: Urban parks are regarded as a promising measure to alleviate urban heat island (UHI) effects. Park cooling effects have been widely investigated, however, the impacts of surrounding 2D/3D landscapes on it remain uncertain, especially in extreme hot weather. Therefore, taking 70 parks in Beijing as the samples, this study investigated the impacts of surrounding 2D/3D landscapes (vegetation, water, impervious surface, and buildings) on the park cooling effects in the extreme hot and normal days. First, based on buffer method, park cooling efficiency (PCE) was determined in the extreme hot and normal days. Then, both 2D (percentage of landscape (PLAND), landscape shape index (LSI), and aggregation index (AI)) and 3D (building density (BD), building height (BH), sky view factor (SVF), and frontal area index (FAI)) metrics were used to explore how surrounding 2D/3D landscapes influence PCE based on boosted regression tree (BRT) approach. The results showed that parks demonstrated the cooling islands, and the average PCE were 7.01 and 7.49 in the extreme hot and normal days, respectively. Surrounding buildings and vegetation metrics are the most important indicator in the extreme hot and normal days, respectively, which account for 30.6% and 47.1% of the contribution of PCE. The relationships between the key surrounding landscape metrics and PCE were nonlinear in the extreme hot and normal days. This study emphasized that surrounding 2D/3D landscapes can significantly affect park cooling effects, and the impacts are nonlinear. The findings are conducive to enhance the park cooling effects by optimizing the surrounding landscapes. Highlights: BRT model was applied to explore the impacts of surrounding 2D/3D landscapes on PCE. Relative importance of surrounding 2D/3D landscape metrics to PCE were analyzed. Marginal effects of key influencing factors to PCE were explored. Rational planning of park surrounding landscapes was proposed.